2007
DOI: 10.1529/biophysj.106.100198
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Cell-Penetrating Peptide Transportan 10 Permeation of Lipid Bilayers

Abstract: The mechanism of the interaction between the cell-penetrating peptide transportan 10 (tp10) and phospholipid membranes was investigated. Tp10 induces graded release of the contents of phospholipid vesicles. The kinetics of peptide association with vesicles and peptide-induced dye efflux from the vesicle lumen were examined experimentally by stopped-flow fluorescence. The experimental kinetics were analyzed by directly fitting to the data the numerical solution of mathematical kinetic models. A very good global… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
271
1
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(293 citation statements)
references
References 46 publications
13
271
1
4
Order By: Relevance
“…They observed that tp10 translocation and membrane pore formation appear to be two independent processes. CF-labeled tp10 was found to rapidly translocate across the lipid bilayer, possibly via a mechanism similar to that suggested by Almeida et al [71]. However the pores, which allow this rapid translocation are small.…”
supporting
confidence: 67%
“…They observed that tp10 translocation and membrane pore formation appear to be two independent processes. CF-labeled tp10 was found to rapidly translocate across the lipid bilayer, possibly via a mechanism similar to that suggested by Almeida et al [71]. However the pores, which allow this rapid translocation are small.…”
supporting
confidence: 67%
“…The mechanism of cell entry of these peptides has been widely studied (13,(17)(18)(19)(21)(22)(23). Although there is still some disagreement on the contribution of spontaneous membrane translocation, in recent years, a consensus has begun to emerge that the highly cationic CPPs (such as Tat and polyarginine) are actively taken up into cells mostly by one or more type of endocytosis (10, 12, 13, 15, 19, 21, 24 -26).…”
mentioning
confidence: 99%
“…11, 28 The helical wheel projection for R 2 W 4 R 2 , R 3 W 4 R 3 and W 3 R 4 W 3 sequences are shown in (Figure 4). According to this projection, these peptides do not show any regular structure.…”
Section: Secondary Structure Predictionmentioning
confidence: 99%